The Hydrogenation dynamics of h-BN sheets - Perim, Eric; Paupitz, Ricardo [UNESP]; Autreto, P. A.S.; Galvao, D. S. (Springer Nature, 2013)
Hexagonal boron nitride (h-BN), also known as white graphite, is the inorganic analogue of graphite. Single layers of both structures have been already experimentally realized. In this work we have investigated, through fully atomistic reactive molecular dynamics simulations, the dynamics of hydrogenation of h-BN single-layers membranes. Our results show that the rate of hydrogenation atoms bonded to the membrane is highly dependent on the temperature and that only at low temperatures there is a preferential bond to boron atoms. Unlike graphanes (hydrogenated graphene), hydrogenated h-BN membranes do not exhibit the formation of correlated domains. Also, the out-of-plane deformations are more pronounced in comparison with the graphene case. After a critical number of incorporated hydrogen atoms the membrane become increasingly defective, lost its two-dimensional character and collapses. The hydrogen radial pair distribution and second-nearest neighbor correlations were also analyzed. © 2013 Materials Research Society.